The role of a designer in the public procurement process of technological investments in water and sewage management - Koszyka, Agata; Zimoch, Izabela (Instal, 2021)
Defining precisely the tasks of individual participants of the investment process in the era of spending EU funds on the improvement of many key elements of the country’s infrastructure, including water and sewage infrastructure, is an extremely important element for the effectiveness of investment activities. The key component of this process is the selection of the author of the design documentation and his role in the investment process, determining the quality and end result of the projects implemented. This article is an attempt to find the role assigned to the author of the design documentation constituting the basis for the description of the subject of the contract for construction investments implemented under the regulations of the public procurement system, based on the example of investments including technological facilities in the water and sewage management. There is a noticeable inconsistency of technical, formal and administrative provisions of the public procurement system, the outline of which is presented in this article. The conducted analysis of public procurement for water supply investments allowed to take the determination of theoretical assumptions regarding the need for the author of the design documentation to make autonomous decisions regarding the application of the best solutions, resulting from the experience and professional knowledge in environmental engineering. In view of the above, the guidelines for the description of the subject of the contract, required from public investors, specified in the zero-one manner appropriate for clear and transparent rules of evaluation and awarding scoring in tender procedures, were analyzed.
Keywords: investment process; designer; water and sewage investments; the Public Procurement Law